2018
DOI: 10.1108/rausp-07-2018-0039
|View full text |Cite
|
Sign up to set email alerts
|

From intention to entrepreneurial action

Abstract: Purpose This paper aims to contribute to the explanatory debate of the entrepreneurial intention-action gap that results from the interposition of normative-regulatory, sociocultural and economic-financial barriers facing potential and intending entrepreneurs. Design/methodology/approach Grounded on post-positivist position, the authors propose a quantitative approach, surveying 569 potential and intending entrepreneurs from a longitudinal and stratified sample of 22 years. Findings The economic-financial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 80 publications
2
12
0
1
Order By: Relevance
“…Thus, Liñán and Fayolle (2015) argued that what promotes or inhibits the creation of a new organization or entrepreneurial action requires a comprehension of how entrepreneurial individuals apprehend and perceive the opportunity based on entrepreneurial characteristics and intentions. Oliveira and Rua (2018) concluded that entrepreneurial characteristics is nurtured via a myriad of relationships between entrepreneurial intentions and action.…”
Section: Development Of Young Entrepreneursmentioning
confidence: 99%
“…Thus, Liñán and Fayolle (2015) argued that what promotes or inhibits the creation of a new organization or entrepreneurial action requires a comprehension of how entrepreneurial individuals apprehend and perceive the opportunity based on entrepreneurial characteristics and intentions. Oliveira and Rua (2018) concluded that entrepreneurial characteristics is nurtured via a myriad of relationships between entrepreneurial intentions and action.…”
Section: Development Of Young Entrepreneursmentioning
confidence: 99%
“…The influence of personal characteristics on entrepreneurial… | 31 Some authors seek to find barriers hindering business. Established barriers differ in various socio-economic characteristics, such as the country, level, and type of education attained, gender, and others (Iskandarini, 2014;Wąsowska, 2016;Oliveira & Rua, 2018;Ng & Fu, 2018;Sitaridis & Kitsios, 2019;and others). Age is also a frequently monitored socio-demographic characteristic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Financial adequacy is necessary for SMEs survival and continuous investment particularly toward training, expansion, education and innovation initiations to build strong comparative advantage (Van Gelderen et al, 2008;Dyer et al, 2014;Markovitch et al, 2014;Bernhofer and Li, 2014;Loizou et al, 2015;De Marco et al, 2016;Arrighetti et al, 2016;Aragon-Sanchez, 2017;Gveroski and Jankuloska, 2017;Oliveira and Rua, 2018;Appiah et al, 2021;Gyamfi et al, 2022). Aragon-Sanchez et al (2017) examined how access to resources affects investment intentions.…”
Section: Financial Resourcementioning
confidence: 99%